Study some mechanical variables for water polo players - Ali Mostafa, Sally (International Journal of Psychosocial Rehabilitation, 2024)
Reliance on applied sciences such as mechanics, physiology, kinetic analysis, and others contributed to improving sports achievement and raising the level of players ’performance, as well as relying on modern techniques in analysis. Water sports of all kinds are among the most important sports in which biomechanics plays an important role in improving achievement. This research aims to design a test for the skill of free swimming with the ball and to identify the values of some kinematic variables for the skill of free swimming with the ball in addition to identifying the relationship between the values of some kinematic variables of the skill of free swimming with the ball. The research sample consisted of registered water polo players in the Alexandria region, and the best (30) players were selected in the free-swimming ball for analysis. The researcher used testing, scientific observation, measurement, and analysis means to collect data, and a video camera was used and quickly (25 pictures) per second to extract the research variables. The descriptive approach was used for its relevance to the nature of the research, and statistical treatments were used (arithmetic mean, standard deviation, and simple correlation coefficient (Pearson). The researcher concluded: • There was a significant positive correlation between achievement and the total number of strokes of the swimming arm with the ball. • There is a significant positive correlation between the total speed of swimming with the ball and the average length of the stroke with the ball. The researcher recommended the following: • To improve the speed of water polo players, emphasis must be placed on increasing the frequency of the stroke with an increase in the length of the stroke with the ball.  while swimming.Emphasis on free-swimming exercises with the ball and at different distances to control the ball• Emphasis on developing the horizontal speed of the water polo player while keeping the ball between the arms • Paying attention to exercises that carry speed with the ball and exercises to control the ball between the arms. • player needs.Conducting other studies, such as studying other types of swimming with the ball that a water polo